Gender, wealth, and participation in community groups in Meru Central District, Kenya - Davis, Kristin E.; Negash, Martha (International Food Policy Research Institute, 2007)
TA mixed-methods, multiple-stage approach was used to obtain data on how gender and wealth affected participation in community groups in Meru, Kenya, and how men and women farmers obtain and diffuse agricultural information. Research techniques included participant observation, documentary analysis, semi-structured interviews, social mapping, group timelines, and structured questionnaires. Dairy-goat farmer groups were interviewed for the study. Qualitative data provided baseline information, and helped in the formulation of research questions. Quantitative data were analyzed using contingency tables, descriptive statistics, correlations, tests of significance, and regression. Factors that affected participation in different types of groups included household composition, age, and gender. Women made up 59 percent of the dairy-goat group (DGG) members, with the DGG project encouraging women’s participation. Women made up 76 percent of DGG treasurer positions; 43 percent of secretary positions, and 30 percent of chairperson positions. Gender also influenced participation in clan groups, water groups, and merry-go-round (savings and loans) groups. Wealth did not appear to have a significant effect on participation in community groups. Extension was the most important information source for both men and women farmers. However, church and indigenous knowledge (passed on from parents) seemed more important to women. Both men and women mentioned other farmers, groups, and “baraza” (public meetings used to make announcements and diffuse information) as important information sources, but they rated them at different levels of importance. Men were diffusing information to greater numbers of people than women, although men and women diffused to similar sources. This study shows that because men and women traditionally participate in different types of groups and receive agricultural information from different sources, development agencies must target different types of groups and institutions to reach men, women, or poor farmers. Mechanisms should be developed to include women, the poor, and other targeted groups in community associations that provide market and other income-earning opportunities.